(untitled) (Tri-Chandra Journal of Anthropology, 2024)
Migration has become a prominent phenomenon where young people migrate to foreign lands or within the country in search of various opportunities like better employment or education. Very little is known about the migration and its impact on the elderly parents who are left behind. The article examines the impact of migration on the life of the elderly people and the change in the role of elderly parents caused by youth out-migration in Dhungkharka of Bethanchok rural municipality, Kavrepalanchowk district. The data was collected by interviewing with the elderly participants. All the interviews were transcribed Verbatim in Nepali and translated into English for thematic analysis. It is very important to analyze and address the issues related to elderly people with regular studies and appropriate policies before the problem becomes persistent. The findings of the study revealed that migration has increased the daily workload of the elderly parents and the land remained either barren or less productive due to shortage of labor. Moreover, they faced different kinds of problems like physical, psychological or emotional problems.